Comparative genomics analysis of escherichia coli: insight into its pathogenicity - Ibrahim, Ahmed Farah Mohamed (2022)
Escherichia coli (E. coli) is a gram-negative bacilli bacterium from the Enterobacteriaceae family that may colonise and survive as a commensal in the infant's gastrointestinal tract (GIT) a few hours after birth, as well as in animals and the environment. E. coli may cause infections in the intestine or extraintestinal organs in both high and low-income nations including in serious invasive diseases such as bacteraemia and sepsis. Furthermore, E. coli is the leading antibiotic resistance organisms such as E. coli sequence type 131 (ST131), an example of a successful multidrug-resistant pandemic clone. The aim of this study was to compare the 22 complete genome strains against 3 local draft genome strains of E. coli and gain insight into their pathogenicity. Pathogenicity comparison between local strains and public strains was investigated based on analysis of 25 strains genomic sequences that were retrieved from the NCBI database. Islandviewer 4 was used to forecast genomic islands. OmicsBox 2.1.14 was employed as a multi-locus sequence typing tool (MLST) to screen for sequence type. The pathogenicity and non-pathogenicity relationship was analysed by constructing a phylogenetic tree using neighbour joining method from MEGA software with 1000 bootstraps based on representative strains of 16S rRNA genes. Result from genome comparison found that 11 of the 25 stains are pathogenic while others non-pathogenic. Seven out of 11 of these pathogenic strains are extremely high pathogenic. Most strains from the same locations in the phylogenetic analysis are found to be clustered together, and two of the local strains (INF13/18/A and INF191/17/A) share a common ancestor with the highly pathogenic strains that produce Shiga toxin (Al Ain and AR-0427), while the third local strain (INF32/16/A) shares a common ancestor with the non-pathogenic laboratory strain K-12 substr. MG1655. Most pathogenic strains for the MLST study came into the ST11 category, while non-pathogenic strains went into the ST10 classification. Our local strains seem to be associated with various sequence types; INF13/18/A is associated with ST156, INF32/16/A with ST354, and INF191/17/A with ST131, which all suggested as pathogen, Extraintestinal E. coli (ExPEC). As conclusion, two of the local strains (INF13/18/A and INF191/17/A) have been identified to be highly pathogenic while INF32/16/A is less pathogenic. In general, since they have less pathogenicity and virulence genes, pathogenicity of local strains is less compared to other 22 strains.